Motor learning and control concepts and applications - Magill, Richard; Anderson, David I. (New York, NY McGraw Hill, 2024)
This 2024 release primarily updates the previous edition by adding more recent research and interpretations of the concepts and theoretical views presented in the twelfth edition. Similar to the previous editions this 2024 release continues its two most distinctive features as an introductory motor learning and control textbook: its overall approach to the study of motor learning and control and the organization of the implementation of that approach. In every release of this book, the overall approach has been the presentation of motor learning and control "concepts" to identify the common theme of each chapter. The concepts should be viewed as generalized statements and conclusions synthesized from collections of research findings. Following the concept statement is a description of a real-world application of the concept, which is then followed by discussions of specific topics and issues associated with the concept. An important part of these discussions are summaries of research evidence, on which we base our present knowledge of each topic and issue, as well as the implications of these knowledge for practitioners. The benefit if this organizational scheme is the presentation of motor learning and control as a set of principles and guidelines for practitioners, which are based on research evidence rather than on tradition or "how things have always been done."
1. The classification of motor skills -- 2. The measurement of motor performance -- 3. Motor abilities -- 4. Neuromotor basis for motor control -- 5. Motor control theories -- 6. Sensory components of motor control -- 7. Performance and motor control characteristics of functional skills -- 8. Action preparation -- 9. Attention as a limited capacity resource -- 10. Memory components, forgetting, and strategies -- 11. Defining and assessing learning -- 12. The stages of learning -- 13. Transfer of learning -- 14. Demonstration and verbal instructions -- 15. Augmented feedback -- 16. Practice variability and specificity -- 17. The amount and distribution of practice -- 18. Whole and part practice -- 19. Mental practice
"This International Student Edition is for use outside of the U.S." -- book cover
2024 Release
Includes bibliographical references and index
Keywords: Motor Learning -- Textbooks